Phytochemicals and PI3K Inhibitors in Cancer—An Insight - Suvarna, Vasanti; Murahari, Manikanta; Khan, Tabassum; Chaubey, Pramila; Sangave, Preeti (Frontiers in Pharmacology, 2017)
In today’s world of modern medicine and novel therapies, cancer still remains to be one of the prime contributor to the death of people worldwide. The modern therapies improve condition of cancer patients and are effective in early stages of cancer but the advanced metastasized stage of cancer remains untreatable. Also most of the cancer therapies are expensive and are associated with adverse side effects. Thus considering the current status of cancer treatment there is scope to search for efficient therapies which are cost-effective and are associated with lesser and milder side effects. Phytochemicals have been utilized for many decades to prevent and cure various ailments and current evidences indicate use of phytochemicals as an effective treatment for cancer. Hyperactivation of phosphoinositide 3-kinase (PI3K) signalling cascades is a common phenomenon in most types of cancers. Thus natural substances targeting PI3K pathway can be of great therapeutic potential in the treatment of cancer patients. This chapter summarizes the updated research on plant-derived substances targeting PI3K pathway and the current status of their preclinical studies and clinical trials.